Manual of travel agency practice / Gwenda Syratt, Jane Archer - Syratt, Gwenda
Now in its third edition, this successful must-have manual is thoroughly updated with new chapters and material, covering issues including: * Technology development - the different types of travel agency systems available, what they do, how they do it and how to use them * The Internet - how it is used to book travel, forecasts for its future use and how travel agenets stand in relation to it * Global distribution systems - how to make bookings, and the new windows-based environment * A full endorsement by Travel Weekly The manual demonstrates correct methods for processing travel reservations, identifying business client needs and suitable documentation. It also shows key facts for the profitable planning, organization and operation of the retail travel agency. Each chapter contains exercises pertinent to the topics covered. Students on any of the large number of courses in travel and tourism (ICM, City & Guilds, ABTA, IATA, UFTAA, BTEC, SCOTVEC, University of Oxford Certificate, Diploma of Vocational Education) will find this book invaluable. * Fully revised edition, absorbing the repurcussions of new technology within the industry. * Practical know-how for anyone seeking a career that involves travel agency work. * Clear and comprehensive - designed with the needs of the student in mind.